2020
DOI: 10.3389/fmicb.2020.577242
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Grain for Green Approaches on Soil Bacterial Community in a Karst Region

Abstract: Soil bacteria participate in nutrient cycling above and below ground to promote ecosystem stability and health. However, the relationship of soil bacteria and environmental factors following the Grain for Green (GfG) program remains poorly understood in southwest China. Soil samples were collected from seven Grain for Green sites that had been revegetated for 15 years. Four of these sites were afforested with a different tree species: Zenia insignis (ZI), Toona sinensis (TS), Castanea mollissima (CM), and Citr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 52 publications
4
9
0
Order By: Relevance
“…After 10 years of vegetation restoration, there were significant differences in soil properties under different vegetation restoration treatments. The related studies have shown that converting land use from agriculture to cultivated pasture reduced soil acidity (Chen et al, 2020), which was consistent with the findings in this study that DG, LP, and LT treatments reduced soil pH. This may be because cultivated pasture has higher aboveground biomass, which can produce a large amount of easily decomposable litter, increase the community of burrowing animals, and accelerate the cation cycle in the grassland ecosystem, thereby offsetting soil acidification (Paudel et al, 2021).…”
Section: Effects Of Different Vegetation Restorations On Soil Propert...supporting
confidence: 90%
See 2 more Smart Citations
“…After 10 years of vegetation restoration, there were significant differences in soil properties under different vegetation restoration treatments. The related studies have shown that converting land use from agriculture to cultivated pasture reduced soil acidity (Chen et al, 2020), which was consistent with the findings in this study that DG, LP, and LT treatments reduced soil pH. This may be because cultivated pasture has higher aboveground biomass, which can produce a large amount of easily decomposable litter, increase the community of burrowing animals, and accelerate the cation cycle in the grassland ecosystem, thereby offsetting soil acidification (Paudel et al, 2021).…”
Section: Effects Of Different Vegetation Restorations On Soil Propert...supporting
confidence: 90%
“…The karst area in southern China with Guizhou as the center reaches 1.24 million km 2 , with the largest area of continuous exposed carbonate rocks and the strongest karst development among the three major karst-concentrated distribution areas in the world ( Xiong et al, 2002 ). The karst parent rock has a slow soil formation rate, shallow soil layers, broken ground, and concentrated rainstorms, especially disturbed by traditional unprotected farming activities, which can easily cause damage to native vegetation, serious soil erosion, and rocky desertification ( Xiong et al, 2017 ; Chen et al, 2020 ; Hu and Lan, 2020 ). Karst rocky desertification is a land degradation process that includes severe soil erosion, extensive exposure of bedrocks, sharp decline in soil productivity, and the emergence of desert-like landscapes, which had become the main ecological disaster that seriously hinders the economic development of southwest China ( Xiong et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was only composed of bacterial OTUs that belonged to both widespread and more narrowly distributed taxa (66). These taxa were related to N² fixation (Rhizobiales, Frankiales, Ktedonobacterales and Acetobacterales), adapted to soil with low content in phosphorus (Gemmatales, Microtrichales and Solibacterales) and involved in soil organic matter degradation (Micrococcales and Thermomicrobiales) (67)(68)(69)(70)(71)(72)(73). Together with the unknown fungal communities, this soil core microbiome represented the specificity of the microbial communities of the fellfield soils of the Kerguelen Islands that were composed of both restricted and cosmopolitan microbes.…”
Section: Restricted and Cosmopolitan Soil Microbiomes Of The Kerguele...mentioning
confidence: 99%
“…For the first path, SOM was negative to soil pH, and then positive to AP and further weakening the bacterial richness. This can attribute to the association between AP and bacterial richness being tight in soils with the limited P [57,58]. In the second path, SOM promoted the storage of water in soils, and then directly negatively associated with bacterial richness and further positively associated with bacterial diversity.…”
Section: Nvr Influenced the Microbial Community In Gullies By The Acc...mentioning
confidence: 99%